Digital Transformation: Innovation and Efficiency in East Java Bawaslu Operational Management - Handoko Sosro Hadi Wijoyo; Abdul Warist; Elika Febrianti (Jurnal Ilmiah Mimbar Demokrasi, 2025)
This research examines the digital transformation in the operational management of Bawaslu East Java, focusing on how digital technology improves efficiency and drives innovation in election oversight. Digital transformation includes process digitalization, integrated systems, and data-driven decision-making, which streamline workflows, reduce costs, accelerate responses, and foster innovation in public services. Using a qualitative approach, the study explores strengths, weaknesses, opportunities, and threats, involving policymakers and technical implementers across 38 districts. Findings highlight that the Rumah Data innovation significantly enhances Bawaslu’s performance by centralizing data management, improving transparency, and increasing responsiveness.The analysis places Rumah Data in a promising strategic position, demonstrating that aggressive development strategies effectively sustain innovation within operations. The research recommends proactive actions to strengthen positive drivers such as capacity building, system integration, and data quality improvement—while mitigating risks that could weaken innovation outcomes.Ultimately, this study concludes that digital transformation is crucial for achieving efficient, transparent, and adaptive election oversight. Immediate and strategic interventions are necessary to ensure Rumah Data continues to deliver long-term organizational benefits and supports the achievement of Bawaslu’s strategic objectives.